1998
DOI: 10.1097/00001756-199807130-00025
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral signs of acute pain produced by application of endothelin-1 to rat sciatic nerve

Abstract: We examined whether endothelin-1 (ET-1), a potent vasoconstrictive peptide secreted in high concentration by metastatic prostate cancer cells, produces endothelin receptor-dependent pain behavior when applied to rat sciatic nerve. ET-1 (200-800 microM) applied to the epineurial surface of rat sciatic nerve produced reliable, robust, unilateral hindpaw flinching lasting 60 min. Pre-emptive systemic morphine completely blocked this effect in a naloxone-reversible manner, suggesting that this behavior was pain-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
100
1
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(107 citation statements)
references
References 7 publications
5
100
1
1
Order By: Relevance
“…Newer ET A -selective antagonists that have greater bioavailability when given orally have been developed and some (e.g., ABT-627 or Atrasentan and BMS-207940) are more potent and more selective than BQ-123 (Murugesan et al 2003;Opgenorth et al 1996;Verhaar et al 2000). However, BQ-123 has been shown to effectively attenuate nocifensive behaviors and hyperalgesia when applied locally to the sciatic nerve (Davar et al 1998 3. Mean Ϯ SE heat-response thresholds of C nociceptors in nontumorbearing (control) and in tumor-bearing (cancer) mice before (baseline) and after injection of vehicle (10 l of PBS) or ET-1 (100 M in 10 l).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Newer ET A -selective antagonists that have greater bioavailability when given orally have been developed and some (e.g., ABT-627 or Atrasentan and BMS-207940) are more potent and more selective than BQ-123 (Murugesan et al 2003;Opgenorth et al 1996;Verhaar et al 2000). However, BQ-123 has been shown to effectively attenuate nocifensive behaviors and hyperalgesia when applied locally to the sciatic nerve (Davar et al 1998 3. Mean Ϯ SE heat-response thresholds of C nociceptors in nontumorbearing (control) and in tumor-bearing (cancer) mice before (baseline) and after injection of vehicle (10 l of PBS) or ET-1 (100 M in 10 l).…”
Section: Discussionmentioning
confidence: 99%
“…For example, injection of ET-1 into the plantar surface of the hind paw evoked dose-dependent hind paw licking (Gokin et al 2001;Menendez et al 2003b;Piovezan et al 2000), and application of ET-1 directly to the sciatic nerve evoked robust hind paw flinching (Davar et al 1998;Fareed et al 2000). Injection of ET-1 into the hind paw also produced tactile allodynia (Balonov et al 2006;McKelvy et al 2007), and mechanical (da Ferreira et al 1989) and heat (Menendez et al 2003b) hyperalgesia.…”
Section: Et-1-evoked Nocifensive Behaviors and Hyperalgesiamentioning
confidence: 99%
See 1 more Smart Citation
“…As ET receptor blockers were found to alleviate acute and chronic pain in several animal models, it was suggested that ETs have nociceptive effects [34,53]. Pomonis et al [135] investigated the distribution of ET receptors in DRG and found that only SGCs and non-myelinating Schwann cells expressed ET B receptors, whereas neurons expressed ET A receptors (see also Ref.…”
Section: Endothelinsmentioning
confidence: 99%
“…ET-1 is a potent vasoconstrictor that can also evoke pain sensations in rodents and humans (14,22,(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). The biological effects of ET-1 are mediated by two distinct GPCRs: endothelin A receptor (ETAR) and endothelin B receptor (ETBR) (37).…”
Section: Introductionmentioning
confidence: 99%